Development of Edutainment and Problem Solving Based Student Worksheet on Magnet Concept for Elementary Science - Aeni, Dewi Nur; Fatmaryanti, Siska Desy; Ngazizah, Nur (Jurnal Paedagogy, 2026)
This study aims to develop a student worksheet integrating edutainment and problem solving approaches to improve fifth grade students’ understanding of magnetism. The research employed a Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and was conducted over four meetings at Muhammadiyah I Elementary School Purworejo, involving limited and large scale trials with 10 and 21–22 students. The data analysis technique used in this study was quantitative descriptive analysis, which included product validity analysis, practicality analysis, effectiveness analysis, and analysis of the improvement in conceptual understanding. The developed student worksheet was validated by a media expert and two material experts, yielding an average validation score of 86.3% (highly valid). The practicality assessment reached 95.2%, categorized as very practical. Pretest and posttest results showed improved student understanding with an average increase of 80.61%. Its effectiveness was further supported by an N-Gain score of 0.8 (high category). These findings indicate that the edutainment and problem solving based student worksheet has strong potential as an effective learning medium for enhancing students’ understanding of magnetic concepts and addressing misconceptions in Integrated Natural and Social Sciences learning at the elementary level.